2014
DOI: 10.1093/aob/mcu250
|View full text |Cite
|
Sign up to set email alerts
|

Aphid-repellent pheromone E-β-farnesene is generated in transgenic Arabidopsis thaliana over-expressing farnesyl diphosphate synthase2

Abstract: Over-expression of FPS2 in the cytosol and targeting of its translated product to chloroplasts in arabidopsis led to synthesis of several novel sesquiterpenes, including E-β-farnesene, and induced alarm responses in M. persicae. The results suggest a potential for engineering aphid-resistant strains of arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Similarly, Kos et al (2013) showed that transgenic Arabidopsis overproducing the terpenoids linalool, nerolidol and 4,8-dimethylnona-1,3,7-triene ((E)-DMNT) were less attractive to the aphid Brevicoryne brassicae L. (Hemiptera: Aphidae). Notably, b-farnesene is an alarm pheromone for aphids, probably facilitating pest dispersion and contributing to the anti-xenotic effect of the host (Bhatia et al, 2014). Some enzymes in the terpenoid pathway, such as b-ocimene synthase, which catalyse the biosynthesis of b-ocimene, are under control of the JA pathway (Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kos et al (2013) showed that transgenic Arabidopsis overproducing the terpenoids linalool, nerolidol and 4,8-dimethylnona-1,3,7-triene ((E)-DMNT) were less attractive to the aphid Brevicoryne brassicae L. (Hemiptera: Aphidae). Notably, b-farnesene is an alarm pheromone for aphids, probably facilitating pest dispersion and contributing to the anti-xenotic effect of the host (Bhatia et al, 2014). Some enzymes in the terpenoid pathway, such as b-ocimene synthase, which catalyse the biosynthesis of b-ocimene, are under control of the JA pathway (Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Two ATCOPIA93-containing genes, AT4G17190 and AT5G20280, which are implicated respectively in defense against aphids and in nectar secretion Bhatia et al 2015), also showed reduced expression, but only at generation F8. In both cases, ATCOPIA93 was located within an intron and either in the same or the opposite orientation relative to gene transcription and was associated with transcript truncation at F8, but not at F16 ( Figure 6C), when the insertions are epigenetically silent.…”
Section: Intronic Atcopia Insertions Create Epigenetically-inducible mentioning
confidence: 99%
“…C-C double bonds in prenyl-PP can be either in trans or cis conformation depending on the PT-trans-PTs form trans isomers, and cis-PTs form cis-isomers. Considering the length of the produced carbon backbone, trans-PTs can be classified as short-chain PTs (C 10-25 ), medium-chain PTs (C [30][31][32][33][34][35], and long-chain PTs (C 40-50 ) [7]. Members of the short-chain ones are in ascending order C 10 geranyl diphosphate synthase (GPPS), C 15 farnesyl diphosphate synthase (FPPS), C 20 geranylgeranyl diphosphate synthase (GGPPS), and C 25 geranylfarnesyl diphosphate synthase (GFPPS) ( Table 1).…”
Section: Trans-prenyltransferasesmentioning
confidence: 99%
“…The longer-variant FPPS1L is targeted to mitochondria, the shorter FPPS1S, together with the FPPS2, is localized to the cytosol. Research on this topic demonstrated that FPPS genes are redundant, thus one copy of the gene is enough to keep plants viable with only small changes in metabolite content [25,[30][31][32][33]. On the other hand, total loss of FPPS activity is lethal due to severely impaired embryo development [31].…”
Section: Trans-prenyltransferasesmentioning
confidence: 99%